1985
DOI: 10.1007/bf01212648
|View full text |Cite
|
Sign up to set email alerts
|

Influence of different inhibitors on the activity of theRAD54 dependent step of DNA repair inSaccharomyces cerevisiae

Abstract: The recombinagenic pathway of DNA repair in yeast was characterized by the effect of different inhibitors on the temperature-dependent survival after gamma-irradiation in haploid cells of the thermoconditional mutant rad54-3. Blocking protein synthesis with cycloheximide in replicating cells caused partial inhibition of the RAD54 dependent function but some repair activity remained detectable. This indicates that gamma-rays can induce RAD54 activity above some constitutive level of function. Inhibition of DNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1986
1986
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…This gene is a homolog of the U. Maydis Rec1 and may function not only in checkpoints but also in some aspects of recombinational repair (Carr, 1995;Lehmann, 1996). Finally, in Saccharomyces cerevisiae, a strong inhibitory e ect of ca eine on the RAD54 mediated repair was reported (Siede et al, 1985).…”
Section: Caffeine Radiosensitization In Yeastmentioning
confidence: 97%
“…This gene is a homolog of the U. Maydis Rec1 and may function not only in checkpoints but also in some aspects of recombinational repair (Carr, 1995;Lehmann, 1996). Finally, in Saccharomyces cerevisiae, a strong inhibitory e ect of ca eine on the RAD54 mediated repair was reported (Siede et al, 1985).…”
Section: Caffeine Radiosensitization In Yeastmentioning
confidence: 97%
“…The tfb3 ts Strain Exhibits Caffeine Sensitivity-In eukaryotic cells, caffeine is known to adversely affect genomic stability, at least in part by inhibiting DNA repair and/or overriding DNA damage checkpoint controls (20,21). In an effort to determine whether UV radiation sensitivity could be increased by inclusion of caffeine in the growth media, we were surprised to observe that tfb3 ts failed to grow in the presence of the drug, whereas the isogenic wild-type strain grew normally (Fig.…”
Section: The Tfb3mentioning
confidence: 99%
“…These early studies incriminated caffeine as an inhibitor of DNA repair mechanisms but without relating the caffeine sensitivity with the DNA repair pathways. In subsequent studies, a pronounced inhibitory effect of caffeine on the Rad54-dependent repair of UV-irradiation damage was reported, an inhibition that was strongly dependent on the concentration of caffeine [ 41 ]. Later, other research groups confirmed the dose-dependent inhibitory effect of caffeine on the Rad54-dependent repair of UV-irradiation damage [ 42 , 43 ].…”
Section: Caffeine: Between Radio-protector and Radio-sensitizermentioning
confidence: 99%
“…A slight caffeine-sensitizing effect was found for the rad5l and rad54 mutants, which show defects in the repair of X-ray induced damage [ 45 ]. The results suggested that caffeine enhanced radiation-induced cell killing and that the caffeine-sensitive process involved in the repair of γ-ray-induced lesions interfered with a recombinational repair mechanism occurring in cells in S or G2 phase [ 41 ].…”
Section: Caffeine: Between Radio-protector and Radio-sensitizermentioning
confidence: 99%